Metabolic Labeling for the Visualization and Identification of Potentially O‐GlcNAc‐Modified Proteins. Issue 2 (14th April 2020) - Pedowitz, Nichole J.; Zaro, Balyn W.; Pratt, Matthew R.
Abstract: O‐GlcNAcylation is a posttranslational modification involving the addition of the single monosaccharide N‐ acetylglucosamine (GlcNAc) onto serine and threonine residues of intracellular proteins. Though O‐GlcNAc is found on ∼1000 proteins in mammals, its specific function on individual substrates remains largely a mystery. To overcome this shortcoming, work has been put toward developing metabolic chemical reporters (MCRs) to label O‐GlcNAcylated proteins for subsequent biochemical analysis. Typically, these MCRs are GlcNAc or GalNAc analogs functionalized with azide or alkyne handles. These unnatural sugar moieties can be metabolically incorporated directly on to protein substrates. The protocols outlined in this article describe how to use MCRs as tools for visualizing and identifying potentially O‐GlcNAc modified proteins via in‐gel fluorescence, Western blotting, and mass spectrometry. Taken together, MCR labeling provides a powerful tool to discover where and when substrates are O‐GlcNAc modified. © 2020 by John Wiley & Sons, Inc. Basic Protocol 1 : Treatment of cells and CuAAC Basic Protocol 2 : In‐gel fluorescence of labeled cell lysates (1 mg scale) Basic Protocol 3 : Enrichment of labeled proteins, trypsinolysis, and collection of peptides for proteomics Basic Protocol 4 : Proteomic identification of labeled proteins